(untitled) (Altre Modernità, 2014)
The present study aims at establishing the taxonomy for the genre of migration literature. It first focuses on the significance of the term ‘migration’ and the motivations that lead people to migrate – be they ‘poverty’ or ‘desire’ to change. The study then proceeds to a discussion of the narratives, both of individual and of collective lives, with specific reference to their recurring themes and stylistic strategies. Finally the study will deal with an analysis of the characters, which very often stand for the authors’ own alterego narrating, in first or third person, fictional or real events, and thus transmitting direct memories of the dramatic events inherent to migration, or memories derived from retrospective narrations of relatives and countrymen. The linearity of such scheme, when duly followed, will allow the insertion of selected texts within a specific tradition, to be defined according to rhetoric continuity, themes and references to common models.